Prognostic Value of Plasma Pentraxin-3 Levels in Patients with Stable Coronary Artery Disease after Drug-Eluting Stent Implantation - Haibo, Liu; Xiaofang, Guo; Chunming, Wang; Jie, Yuan; Guozhong, Chen; Limei, Zhang; Yong, Cao; Yu, Fang; Yingchun, Bao; Wangjun, Yu; Junbo, Ge (Mediators of Inflammation, 2014)
Pentraxin-3 (PTX3) is an inflammatory marker thought to be more specific to cardiovascular inflammation than C-reactive protein (CRP). Our aim was to assess the prognostic value of PTX3 in patients with stable coronary artery disease (CAD) after drug eluting stent (DES) implantation. Plasma PTX3 levels were measured before percutaneous coronary intervention (PCI) and at 24 h post-PCI in 596 consecutive patients with stable CAD. Patients were followed up for a median of 3 years (range 1–5) for major adverse cardiovascular events (MACEs). We found that the post-PCI plasma PTX3 levels were significantly higher at 24 h after PCI than pre-PCI, patients with MACEs had higher post-PCI PTX3 levels compared with MACEs-free patients, patients with higher post-PCI PTX3 levels (median > 4.384 ng/mL) had a higher risk for MACEs than those with PTX3 < 4.384 ng/mL, and post-PCI PTX3, cTnI, multiple stents, and age but not high-sensitivity CRP (hsCRP) were independently associated with the prevalence of MACEs after DES implantation. The present study shows that post-PCI PTX3 may be a more reliable inflammatory predictor of long-term MACEs in patients with stable CAD undergoing DES implantation than CRP. Measurement of post-PCI PTX3 levels could provide a rationale for risk stratification of patients with stable CAD after DES implantation.